2009
DOI: 10.1016/j.jada.2009.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol-Deficient and High-Phytosterol Diets Developed for Controlled Feeding Studies

Abstract: Phytosterols reduce cholesterol absorption and low-density lipoprotein (LDL) cholesterol concentrations, but the quantity and physiological significance of phytosterols in common diets are generally unknown because nutrient databases do not contain comprehensive phytosterol data. The primary aim of this study was to design prototype phytosterol-deficient and high-phytosterol diets for use in controlled feeding studies of the influence of phytosterols on health. A second aim was to quantify the phytosterol cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…In terms of TC and LDL-C concentrations, this is well established because replacement of saturated fatty acids with polyunsaturated and monounsaturated fatty acids diminishes these parameters [22]. Additional higher contents of phytosterols in the vegan diet may cause a lipidlowering effect [8]. Our study also confirms recent reports observed by Bradbury et al [23] in the large European population which show positive results in reduction of apoB and also a lower concentration of non-HDL-C in the vegan group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In terms of TC and LDL-C concentrations, this is well established because replacement of saturated fatty acids with polyunsaturated and monounsaturated fatty acids diminishes these parameters [22]. Additional higher contents of phytosterols in the vegan diet may cause a lipidlowering effect [8]. Our study also confirms recent reports observed by Bradbury et al [23] in the large European population which show positive results in reduction of apoB and also a lower concentration of non-HDL-C in the vegan group.…”
Section: Discussionsupporting
confidence: 87%
“…Of particular importance may also be a greater supply of phytosterols, plant derived compounds similar to cholesterol which have lipid-lowering properties. Phytosterols reduce absorption of cholesterol in the digestive tract and influence lipoprotein metabolism, which in turn may lead to a decrease in total cholesterol (TC) and low density lipoprotein (LDL) cholesterol (LDL-C) concentration [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, serum levels rise with increasing intake and can reflect a potentially beneficial effect of reduced cholesterol absorption efficiency. 1 On the other hand, it is well established that serum phytosterol levels are also positively correlated with intrinsic cholesterol absorption efficiency, a potentially harmful characteristic that may predispose to coronary heart disease. 2 Therefore, we believe that simple serum phytosterol levels have limited utility in epidemiological studies because it is not clear what elevated levels represent.…”
mentioning
confidence: 99%
“…The hydroxyl group at C3 is linked to a hexose or a 6-fatty-acyl hexose moiety for phytosterol glucosides and acyl glucosides, respectively [32]. Glycosylated phytosterols are present in particular foods and plants, and efficiently lower plasma cholesterol levels [33][34][35][36][37]. It is unclear to what extent phytosterol glucosides are formed from non-modified phytosterols within the body.…”
Section: Introductionmentioning
confidence: 99%